Pengaruh Motivasi Kerja Terhadap Produktivitas Kerja Pegawai Pada Puskesmas Tataba Kecamatan Buko: The Effect of Work Motivation On Employee Work Productivity At Tataba Puskesmas Buko District - Yulandari Buraera; Sri Mulyaningsih Kamaru (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2022)
Human resources or good employees will certainly experience setbacks, so motivation is needed to increase work productivity. After giving motivation, there must be output produced to achieve the target, with this encouragement, which will make employees more productive at work. This study aimed to determine the effect of work motivation on employee productivity at the Tataba Health Center, Buko District. The type of research used in this study is a quantified qualitative research type, so it uses Likert. Data collection techniques include a questionnaire with the withdrawal technique of Simple Random Sampling. The research sample used was 26 people who became employees at the Tataba Health Center, Buko District. The analytical tool used is simple linear regression in the equation, Y = a + bX, correlation coefficient, coefficient of determination, and t-test (statistical test). The partial t-test data analysis results have a significant effect on work motivation on employee productivity at the Tataba Health Center, Buko District.